Beyond Feature Binding: Interference from Episodic Context Binding Creates the Bivalency Effect in Task-Switching - Meier, Beat; Rey-Mermet, Alodie (Frontiers in Psychology, 2012)
When switching between different tasks and bivalent stimuli occur only occasionally on one of them, performance is slowed on subsequent univalent trials even if they have no overlapping features with the bivalent stimulus. This phenomenon has been labeled the “bivalency effect”. Recent evidence has revealed that this effect is robust, general, and enduring. Moreover, it challenges current theories of task switching and cognitive control. Here, we review these theories and propose a new, episodic context binding account. According to this account, binding does not only occur between stimuli, responses and tasks, but also for the more general context in which the stimuli occur. The result of this binding process is a complex representation that includes each of these components. When bivalent stimuli occur, the resulting conflict is associated with the general context, creating a new conflict-loaded representation. The reactivation of this representation causes interference on subsequent trials, that is, the bivalency effect. We evaluate this account in light of the empirical evidence.